2012
DOI: 10.1002/app.34908
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of polyurethane (urea)/modified nano‐calcium carbonate hybrid aqueous dispersions and their films

Abstract: This investigation was focused on properties of polyurethane (urea) (PUU) by incorporating silica sol-modified nano-calcium carbonate (CaCO 3 ). The FT-IR spectroscopy and f potential measurement indicated the presence of a hybrid effect due to the hydrogen bonding between the nano particles and the polymer matrix. For these hybrid aqueous dispersions, the particle size decreased as the modified nano-CaCO 3 content increased, and the polydispersity index was very narrow (<1.20). Films prepared with the hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…CaCO 3 has the advantages of wide distribution in nature, simple preparation methods, and biocompatibility 51–53 . PU/nano‐CaCO 3 composites have good mechanical properties, thermal stability, and shape memory behavior; adding CaCO 3 can also reduce the cost of composites 21,52–54 …”
Section: Effect Of Filler Typementioning
confidence: 99%
See 4 more Smart Citations
“…CaCO 3 has the advantages of wide distribution in nature, simple preparation methods, and biocompatibility 51–53 . PU/nano‐CaCO 3 composites have good mechanical properties, thermal stability, and shape memory behavior; adding CaCO 3 can also reduce the cost of composites 21,52–54 …”
Section: Effect Of Filler Typementioning
confidence: 99%
“…In the study of Yang et al, 53 M‐CaCO 3 (nano‐CaCO 3 modified by nano‐SiO 2 particles enriched surface OH) was dispersed homogeneously in PU matrix by in situ dispersing method. FTIR spectra showed that the amount of hydrogen‐bonded CO and hydrogen‐bonded NH increased.…”
Section: Effect Of Filler Typementioning
confidence: 99%
See 3 more Smart Citations